2016
DOI: 10.5468/ogs.2016.59.4.295
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of falsely elevated risk of ovarian malignancy algorithm in women with ovarian endometrioma

Abstract: ObjectiveTo estimate the incidence of falsely elevated risk of ovarian malignancy algorithm (ROMA) in a group of women with pathologically confirmed endometrioma and to investigate the associated factors.MethodsOne hundred premenopausal women surgically diagnosed with ovarian endometrioma were selected. Preoperative clinical, laboratory, and surgical characteristics were compared between the elevated-risk group (ROMA-premenopausal value, ≥7.4%) and normal-risk group (ROMA-premenopausal value, <7.4%).ResultsEle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…There are likely other factors influencing the concentrations of HE4, CA125, and ROMA. Shin et al found falsely elevated ROMA in women with confirmed ovarian endometrioma, which was likely due to the elevated serum HE4.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There are likely other factors influencing the concentrations of HE4, CA125, and ROMA. Shin et al found falsely elevated ROMA in women with confirmed ovarian endometrioma, which was likely due to the elevated serum HE4.…”
Section: Discussionmentioning
confidence: 98%
“…Shin et al 20 found falsely elevated ROMA in women with confirmed ovarian endometrioma, which was likely due to the elevated serum HE4.…”
Section: Ta B L E 3 Case-control Studymentioning
confidence: 96%
“…Because HE4 showed higher specificity than CA 125, it has been identified as a tumor marker for ovarian cancer [6]. Even in endometriosis, HE4 was less affected than CA 125 [78]. When HE4 was used together with CA 125 to detect ovarian cancer, sensitivity and specificity were enhanced [9].…”
Section: Introductionmentioning
confidence: 99%